Pharmacokinetics and relative bioavailability of meloxicam oil suspension in pigs after intramuscular administration. Issue 2 (27th December 2019) - Li, Ying; Guo, Fanxi; Jiang, Xiangyuan; Ren, Juncai; Miao, Yingxue; Ding, Fangyi; Yu, Zugong
Abstract: This study aimed to develop one novel meloxicam (MEL) oil suspension for sustained‐release and compare the pharmacokinetic characteristics of it with MEL conventional formulation in pigs after a single intramuscular administration. Six healthy pigs were used for the study by a crossover design in two periods with a withdrawal interval of 14 days. Plasma concentrations of MEL were measured by ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS). Pharmacokinetic parameters were calculated by noncompartmental methods. The difference was statistically significant ( p < .05) between MEL oil suspension and MEL conventional formulation in pharmacokinetic parameters of mean residence time (6.16 ± 4.04) hr versus (2.66 ± 0.55) hr, peak plasma concentration ( C max ) (0.82 ± 0.12) µg/ml versus (1.12 ± 0.22) µg/ml, time needed to reach C max ( T max ) (2.33 ± 0.82) hr versus (0.59 ± 0.18) hr, and terminal elimination half‐life ( t 1/2λz ) (3.74 ± 2.66) hr versus (1.55 ± 0.37) hr. The mean area under the concentration–time curve (AUC0–∝ ) of MEL oil suspension and MEL conventional formulation was 5.35 and 3.43 hr µg/ml, respectively, with a relative bioavailability of 155.98%. Results of the present study demonstrated that the MEL oil suspension could prolong the effective time of drugs in blood, thereby reducing the frequency of administration on a course of treatment. Therefore, the novel MEL oil suspension seems to be of great value in veterinary clinical application.